The Effect of Accounting Information Systems on Internal Control of Fuel Oil Inventories at Public Fuel Filling Stations on Lombok Island - Maulidi, Muhammad Gilang; Lestari, Baiq Anggun Hilendri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine how much the accounting information system affects the internal control of fuel inventory, with the hope of providing useful recommendations for gas station managers in improving their operational and financial performance. This research was designed as associative research with a quantitative approach. The data collection method uses primary data. The sample for this research was 41 gas stations. This research uses a simple linear regression analysis method with the SPSS version 29 test tool. The study results show that the accounting information system has a significant positive effect on internal inventory control. This is proven by the values with and. Implementing an accounting information system influences internal control of fuel supplies by 69.6%. Other variables influence the remaining 30.4%. This shows that the internal inventory control generated by a company is better if the company uses a better accounting information system.